2013
DOI: 10.1162/artl_a_00105
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning in a Chemical Perceptron

Abstract: A version of this paper with color figures is available online at http://dx.doi.org/10.1162/ artl_a_00105. Subscription required.Abstract Autonomous learning implemented purely by means of a synthetic chemical system has not been previously realized. Learning promotes reusability and minimizes the system design to simple input-output specification. In this article we introduce a chemical perceptron, the first full-featured implementation of a perceptron in an artificial (simulated) chemistry. A perceptron is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…Banda et al [48,49] have simulated several kinds of trainable perceptron using artifical chemistry, which is conceptually similar to our work but was designed using more abstract chemical reactions. It has been shown that such arbitrary systems of chemical reactions can be faithfully implemented in a biochemical setting by compiling them into an enlarged system of DNA strand displacement reactions [50].…”
Section: Related Workmentioning
confidence: 98%
“…Banda et al [48,49] have simulated several kinds of trainable perceptron using artifical chemistry, which is conceptually similar to our work but was designed using more abstract chemical reactions. It has been shown that such arbitrary systems of chemical reactions can be faithfully implemented in a biochemical setting by compiling them into an enlarged system of DNA strand displacement reactions [50].…”
Section: Related Workmentioning
confidence: 98%
“…To describe and highlight the main features of the ASP, we will compare it with the WRP [4] in the remainder of this paper. The WRP has two types of species and reaction symmetries.…”
Section: Model and Designmentioning
confidence: 99%
“…P reversibility, to prevent an infinite loop, we must precisely time the recovery phase and have a special species catalysing (guarding) the comparison. We implemented this rather cumbersome mechanism for the WLP as described previously [4]. An improved symmetric strategy is to compare the concentrations of species indirectly by their impact on the concurrent reactions they catalyse, and so annihilation occurs at the level of complementary products.…”
Section: (I) the Problem Of Negative Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…This has allowed us to study the same system and modify its simulation dynamics from separate campuses. We have successfully applied COEL as a sole tool to model and evaluate various chemical perceptrons (Banda et al, 2013, chemical delay lines, and time-series learners Moles et al, 2015).…”
Section: Introduction and Related Workmentioning
confidence: 99%